2021
DOI: 10.32674/jis.v11i2.1379
|View full text |Cite
|
Sign up to set email alerts
|

Loneliness among African international students in Portugal

Abstract: International students constitute an important sojourner group. This study examined the levels and predictors of loneliness among international students. The sample included 188 Angolan and 210 Cape Verdean college students who attended Portuguese institutions of higher education and a control group of 221 domestic students. The relative strengths of background and acculturation factors in loneliness, as indicators of psychological adaptation, were explored. Results showed that international students reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
0
8
0
Order By: Relevance
“…A number of common experiences emerged. From a positive point of view, we could argue that their experience of moving to Portugal and integrating into Portuguese society was ‘easier’ due to shared language and some level of cultural familiarity, to the extent that host institutions tended to overlook their needs as international students ( Ambrósio et al, 2017 ; see also Neto, 2021 ; Santos, 2020 ; Sin et al, 2019 ). Being more circumspect, we also observed that students from the former Portuguese African colonies were highly dependent on programmes created by the government of Portugal or home country administrations, with systematic problems reported about the late payment of scholarships, with waits of up to four months after the start of exchanges, and grants being pegged at levels insufficient to cover basic living cost (see also Ambrósio et al, 2017 ; Doutor and Alves, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A number of common experiences emerged. From a positive point of view, we could argue that their experience of moving to Portugal and integrating into Portuguese society was ‘easier’ due to shared language and some level of cultural familiarity, to the extent that host institutions tended to overlook their needs as international students ( Ambrósio et al, 2017 ; see also Neto, 2021 ; Santos, 2020 ; Sin et al, 2019 ). Being more circumspect, we also observed that students from the former Portuguese African colonies were highly dependent on programmes created by the government of Portugal or home country administrations, with systematic problems reported about the late payment of scholarships, with waits of up to four months after the start of exchanges, and grants being pegged at levels insufficient to cover basic living cost (see also Ambrósio et al, 2017 ; Doutor and Alves, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Wawera and MacCamley (2020) suggested that international students who sought less support through international student support services while they were studying in the UK tended to feel more lonely. Neto (2021) found that financial challenges, perceived discrimination, and cultural adaptability predicted loneliness experienced by international students in Portugal. Maleku and colleagues (2022) discovered that higher level of loneliness was likely to lead to higher level of anxiety among international students in the US.…”
Section: Loneliness and International Direct Entry Studentsmentioning
confidence: 94%
“…Smith, 2020). A poor financial position may be associated with psychological distress (Neto, 2021). Families tend to be the main source of financial support for international students, followed by scholarships and paid work (Kukatlapalli et al, 2020).…”
Section: Financial Issuesmentioning
confidence: 99%
“…Same-culture networks and strong relationships between international and local students may be useful for students in dealing with this form of loneliness. While all students may feel homesick and lonely, international students may have greater levels of loneliness than local students (Neto, 2021). Many international students are from cultural backgrounds where strong family ties and friendship networks are emphasised (Marginson et al, 2010).…”
Section: Psychological Adjustment Experiencesmentioning
confidence: 99%